Crossroads of bioethics and public health - Darras, Christian (Acta Bioethica, 2004)
In their respective development, medical ethics, as well as public health, reached a crossing point. This process provokes a tension amongst the principles of medical ethics, due to the contradictions aroused between the individual and the social. Nevertheless, the search of new values can help to highlight this apparent opposition. In this manner, medical ethics brings its valuable method of open and contradictory debate, while public health shows a tradition of organization of health activities based on social concepts (solidarity, responsibility, intercultural focus). In addition, in this way, it is also possible to explore the actual conditions for the exercise of medical ethics in the field of health services.